2017
DOI: 10.1190/geo2016-0045.1
|View full text |Cite
|
Sign up to set email alerts
|

Fracture clustering effect on amplitude variation with offset and azimuth analyses

Abstract: Traditional amplitude variation with offset and azimuth (AVOAz) analysis for fracture characterization extracts fracture properties through analysis of reflection AVOAz to determine anisotropic parameters (e.g., Thomsen's parameters) that are then related to fracture properties. The validity of this method relies on the basic assumption that a fractured unit can be viewed as an equivalent anisotropic medium. As a rule of thumb, this assumption is taken to be valid when the fracture spacing is less than λ∕10. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…The effects of fractures on seismic wave propagation strongly depend on the relation between the characteristic size of the fractures, their separation, and the prevailing seismic wavelengths (e.g., Fang et al, 2017). Many analytical and numerical models have been proposed to study seismic wave propagation in rocks containing cracks or fractures that are much smaller than the wavelengths (e.g., Chapman, 2003;Gurevich, 2003;Hudson, 1980;Rubino et al, 2013;Schoenberg & Douma, 1988;Sil, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of fractures on seismic wave propagation strongly depend on the relation between the characteristic size of the fractures, their separation, and the prevailing seismic wavelengths (e.g., Fang et al, 2017). Many analytical and numerical models have been proposed to study seismic wave propagation in rocks containing cracks or fractures that are much smaller than the wavelengths (e.g., Chapman, 2003;Gurevich, 2003;Hudson, 1980;Rubino et al, 2013;Schoenberg & Douma, 1988;Sil, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Section 3.1, it can identify the cluster width in the case where fractures occur in clusters and indicate if there is any correlation between the location of such clusters and large fractures. Determining fracture clusters and their properties are important in studying seismic signatures because they can cause AVAz/AVO responses to deviate from those predicted by effective medium theory (Fang et al, 2017). Barabosa et al (2018) suggested that the presence of fracture clusters can result in two frequency regimes of seismic attenuation and velocity dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Probably the most remarkable manifestation of the presence of fractures embedded in an otherwise isotropic background is the effective anisotropic behavior of seismic waves. This has made the analysis of reflection amplitude variations with offset and azimuth (AVOAz) a common and successful practice for retrieving practically important parameters of the fractured formation such as, for example, the density and the azimuthal orientation of the fractures, as well as the type of saturating pore fluid (e.g., Bakulin et al, 2000;Shen et al, 2002;Fang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%